Neck and shoulder muscle activity and posture among helicopter pilots and crew-members during military helicopter flight. (April 2016) - Murray, Mike; Lange, Britt; Chreiteh, Shadi Samir; Olsen, Henrik Baare; Nørnberg, Bo Riebeling; Boyle, Eleanor; Søgaard, Karen; Sjøgaard, Gisela
Abstract: Neck pain among helicopter pilots and crew-members is common. This study quantified the physical workload on neck and shoulder muscles using electromyography (EMG) measures during helicopter flight. Nine standardized sorties were performed, encompassing: cruising from location A to location B (AB) and performing search and rescue (SAR). SAR was performed with Night Vision Goggles (NVG), while AB was performed with (AB+NVG) and without NVG (AB−NVG). EMG was recorded for: trapezius (TRA), upper neck extensors (UNE), and sternocleido-mastoid (SCM). Maximal voluntary contractions (MVC) were performed for normalization of EMG (MVE). Neck posture of pilots and crew-members was monitored and pain intensity of neck, shoulder, and back was recorded. Mean muscle activity for UNE was ∼10% MVE and significantly higher than TRA and SCM, and SCM was significantly lower than TRA. There was no significant difference between AB−NVG and AB+NVG. Muscle activity in the UNE was significantly higher during SAR+NVG than AB−NVG. Sortie time (%) with non-neutral neck posture for SAR+NVG and AB−NVG was: 80.4%, 74.5% (flexed), 55.5%, 47.9% (rotated), 4.5%, 3.7% (lateral flexed). Neck pain intensity increased significantly from pre- (0.7 ± 1.3) to post-sortie (1.6 ± 1.9) for pilots ( p  = 0.028). If sustained, UNE activity of ∼10% MVE is high, and implies a risk for neck disorders.